Mosaicism for trisomy 3q arising from an unbalanced, de novo t(3;15). Issue 6 (June 1997) - Stallings, R; Vaughn, D; Hall, K; Joyce, C; Ryan, F; Barton, D; Geraghty, M
Abstract : We report on a 2 1/2 year old girl who is dysmorphic, developmentally delayed, and mosaic for an unbalanced, de novo translocation between chromosomes 3 and 15. The karyotype from peripheral blood lymphocytes is 46, XX (50) and the karyotype from skin fibroblasts is 46, XX (28)/46, XX, der(15)t(3;15)(q11;p11) (23). The mechanism for the generation of this unbalanced, de novo translocation is discussed.